Dynamo programming applied to the development of sustainable engineering projects via BIM methodology - Silva, Kevin Maurício Guedes; dos Santos, Natália Victória; Rodrigues, Glauco José de Oliveira; Ribeiro, Danielle Malvaris (Seven Editora, 2024)
In the context of reinforced concrete, one of the main challenges faced by execution professionals is the correct interpretation and understanding of structural projects. The lack of proper understanding of these technical drawings can lead to a series of problems, such as: assembly errors, lack of compliance with current technical standards and even compromising the structural safety of the building. On the other hand, engineers and designers face their own challenges, especially about the time required to prepare the drawings. The pressure of tight deadlines often results in projects being drafted in a hurry, which can lead to significant design errors. In this context, the present work proposes an innovative solution: the development of a set of scripts using the Dynamo software aimed at structural engineering activities. These scripts are primarily intended to streamline the design process from conception to detailing. By automating repetitive and error-prone tasks, scripts not only reduce the time required to draw up drawings, but also significantly improve the final quality of formwork and reinforcement designs. DOI:https://doi.org/10.56238/sevened2024.018-078